Effect of hydrolyzed copra meal separately or in combination with Bacillus cereus var. toyoi on growth performance of broiler chickens - Duarte, Karina Ferreira [UNESP]; Ibuki, Masahisa; Fukui, Kensuke; Kato, Masayoshi; Santos, Elaine Talita [UNESP]; Junqueira, Otto Mack [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
The effects of mannanase-hydrolyzed copra meal (MCM) and MCM + probiotic Bacillus cereus var. toyoi (TY) on growth performance and gut morphometry of broiler chickens were investigated. A total of 1120-one-day-old Cobb chicks were distributed in a completely randomized design with 4 diet treatment groups. Dietary treatments were (1) negative control; (2) positive control (avilamycin 10 ppm); (3) 0.1% MCM for basal diets (4) 0.1% MCM + 0.05% TY. The best feed conversion ratio (FCR), body weight (BW), productivity index (PI) was obtained with 0.1% MCM + 0.05% TY at 42 days of age. With regard to productivity index, every supplementation group had a better rate when compared to that in negative group. Although 0.1% MCM supplemented alone is worse than positive group, it reveals a significantly better value than when it is combined with 0.1% MCM and 0.05% TY. The combination of mannanase-hydrolyzed copra meal with Bacillus cereus var. toyoi improved broiler performance and duodenum and jejunum mucous morphometry, when compared to the negative, positive and 0.1% MCM alone supplementation groups. The combination of MCM and TY probiotics is capable of improving intestinal morphology by behaving like a good growth promoter, with possibility of being an alternative to antibiotics.

Foram investigados os efeitos da farinha hidrolisada da torta de coco (MCM) e MCM + probiótico Bacillus cereus var. toyoi (TY) sobre o desempenho e morfometria intestinal de frangos de corte . Foram utilizados 1.120 pintos de corte da linhagem Cobb 500, distribuídos em delineamento inteiramente casualizado, com quatro tratamentos e dez repetições de 28 aves cada. Os tratamentos foram: (1) controle negativo, (2) controle positivo (avilamicina 10 ppm), (3) 0,1% MCM na dieta controle negativo, (4) 0,1% MCM + 0,05% TY na dieta controle negativo. A melhor conversão alimentar (CA), o peso corporal (PC) e o índice de produtividade (IP) foram obtidos no tratamento com 0,1% MCM + 0,05% TY aos 42 dias de idade. A combinação da farinha hidrolisada da torta de coco com o Bacillus cereus var. toyoi melhorou o desempenho e a morfometria da mucosa do duodeno e do jejuno, quando comparado com os grupos controle negativo, positivo e 0,1 % MCM isoladamente. A combinação do MCM com o TY tem potencial para melhorar a morfologia intestinal, comportando-se como um bom promotor de crescimento com possibilidade de alternativa aos antibióticos.
Efeito da farinha hidrolisada da torta de coco, isoladamente ou em combinação com Bacillus cereus var. toyoi, sobre o desempenho de frangos de corte
Keywords: avilamicina; mannanase-hidrolisada da torta de coco; prebiótico; probiótico; avilamycin; mannanase-hydrolyzed copra meal; prebiotics; probiotics